Etnomatematika pada Budaya Sasak di Rumah Adat Bale Tani Desa Rembitan Sebagai Sumber Belajar Matematika - Baiq Alma Rohviana; M. Habib Husnial Pardi (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
Bale Tani is a traditional traditional house inhabited by the Sasak tribe, which is generally used as a residence. The word "Bale" means house, while "Tani" comes from the Sasak language which means farmer. This research aims to explore the mathematical concepts found in Sasak culture in the Bale Tani traditional house in Rembitan Village as a source of learning and understanding the implementation of ethnomathematics in Sasak culture in Bale Tani traditional house in Rembitan Village in mathematics learning. This research uses qualitative research with an ethnographic approach that describes culture, where the data used is observation, interviews and documentation. The results of this research show that in the Bale Tani traditional house there is a geometric concept such as building flat and building space in the Bale Tani traditional house. The flat shapes found include trapezoidal shapes on the roof of the Bale Tani traditional house when seen from the front, Rectangular shapes on the door shape of the Bale Tani traditional house, Triangle shapes on the roof of the Bale Tani traditional house when seen from the side, Square shapes found on the shape ceiling or ceiling of the Bale Tani traditional house. Meanwhile, the spatial structure found in the Bale Tani traditional house is that the shape of the stairs in the Bale Tani traditional house looks like a block.